(untitled) (Journal of the College of Basic Education, 2022)
Copper nanoparticles (Cu NPs) have synthesized via reduction of copper (II) sulfate pentahydrate salt (Cu SO4 .5H2O) using ascorbic acid as reducing and polyvinyl pyrrolidone PVP (M.Wt 10,000) as a stabilizing agents in presence of Metronidazole Benzoate (MTZ.B) (1-(2-benzyloxy ethyl)-5-nitro methyl imidazole) drug by chemical method. The resulting Cu NPs were characterized by "UV–Vis spectroscopy, atomic force microscopy (AFM), X-ray diffraction (XRD) and FT-IR spectroscopy".